Measurement Of Nose Radius And Wear Of Multiple Cutting Tool Inserts From 2-D Scanned Images With Sub-Pixel Edge Detection - Lim , Teong Yeong (2015)
The nose radius of a cutting tool insert is known to affect the surface quality of the finished workpiece, machining stability, power input as well as the condition of the insert due to the direct interaction of the tool nose with the workpiece during machining. Conventional approaches for measuring the nose radius using profile projector and toolmaker’s microscope require manually selected points from the nose profile which cause inaccurate measurement of nose radius since only a few points from the sector of an imperfect circle from the nose edge are selected. A novel approach for the measurement of nose radius and wear of multiple cutting inserts using 2-D images scanned using a high resolution low-cost flatbed scanner is proposed. Investigation on the effect of scanner’s lighting conditions, tool orientation and location on the accuracy of sub-pixel edge detection of nose radii were carried out. The results of the measurement of nose radii using the scanner approach were compared with a profile projector and the variable-focus 3-D metrology system (Alicona InfiniteFocus). The polar-radius transformation method was used to calculate the projected wear area, Ap and maximum nose flank wear, VBc(max) before and after machining using images from scanner and InfiniteFocus. The measurement of the nose radii of multiple inserts yielded average error of less than 1%. The digital profile projector method yielded a highest error of about 11% in nose radii measurement. For the projected nose wear and nose flank measurement, the maximum deviation are about 6% with a slight underestimation of nose wear for scanner due to the resolution difference between the two scanning methods. Thus, the low-cost and high accuracy approach proposed in this study enables fast and accurate assessment of multiple tools and provides a new solution for tool nose inspection and wear measurement.